Water proporcional meters used as a tool for integrated water management. - Fuentes Barrera, Guillermo Andrés; Guerrero Erazo, Jhoniers (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Good water management is based on the measurement of water flows at different places of the water supply system: water intake, influent and effluent of treatment plants, inlet and outlet of storage tanks, etc. This research aimed to calibrate a proportional flow meter device prototype in order to establish it as a reliable, low-cost, easily suitable for construction, and low maintenance requirement alternative for flow measurement. As a first activity, the flow rate of the device was determined (flow higher that 4.03 m3/h) but the average error was too high (estimated in 21%). After this, regression models were established in smaller flow intervals in order to determine the error for each interval range. Finally, using this information, an optimal flow (higher than 9.21 m3/h, with an error of 8.2%) was determined. The results showed hat the proportional flow meter device is an accurate alternative to measure the water flow at different places of water supply systems for rural communities or small towns. It was demonstrated that construction, installation and operation costs of the device is lower in comparison with mechanical flow meters.